Efeito adjuvante e potencial imunoestimulador das lectinas de Artocarpus integrifolia (KM+ e Jacalina) e Synadenium carinatum (ScLL) na imunização de camundongos contra Neospora caninum - Cardoso, Mariana de Resende Damas (2011)
Lectins are proteins that bind specifically to carbohydrates and have important role in modulation of the immune response. KM+ and Jacalin (JAC) are lectins from the seeds from jackfruit (Artocarpus integrifolia) and ScLL is a lectin from the Synadenium carinatum latex. Neospora caninum is an apicomplexan parasite that causes neuromuscular disease in dogs and reproductive disorders in cattle, with serious economic impact on the livestock industry. The immunestimulatory role of plant lectins has been investigated in several parasitic infections, but not in neosporosis. This study aimed to evaluate the adjuvant effect and the immunestimulatory potential of KM+, JAC and ScLL in immunization of mice against neosporosis. C57BL 6 mouse groups were subcutaneously immunized three times at 15-day intervals with Neospora lysate antigen (NLA) associated with lectins (NLA+KM, NLA+JAC and NLA+ScLL groups), NLA alone, lectins alone (KM, JAC and ScLL groups), and PBS group (infection control). Animals were challenged with Nc-1 isolate (2x107 tachyzoites) and evaluated for morbidity, mortality, specific antibody response, cytokine production by spleen cells, cerebral parasite burden and histopathological lesions. Serological assays demonstrated higher levels of IgG to N. caninum for NLA+KM and NLA+ScLL than NLA+JAC and NLA groups. NLA+KM group induced higher levels of IgG2a isotype whereas NLA+ScLL induced higher levels of IgG1 isotype. In all groups, IgG1 response was higher than IgG2a response before and after challenge, but the IgG2a/IgG1 ratio increased after challenge in NLA+KM, NLA+ScLL and KM groups. Cytokine production after in vitro antigenic stimulation showed that NLA+KM induced high levels of IFN-g and IL-10, presenting the highest IFN-g/IL-10 ratio, followed by NLA+ScLL group, indicating a pattern of immune response toward Th1 type. NLA+JAC induced low levels of these cytokines and the lowest IFN-g/IL-10 ratio in relation to other groups, indicating a profile of Th2 type immune response. After parasite challenge, NLA+KM mice showed the highest survival with low brain parasite burden and moderate tissue inflammation, whereas NLA+ScLL mice presented intermediate survival with low brain parasite burden and low scores of morbidity and inflammation. NLA+JAC group exhibited intermediate survival, but with the highest brain parasite burden and mild inflammation. In conclusion, KM+ and ScLL lectins showed suitable adjuvant effect by increasing NLA immunogenicity and immunostimulatory role by conferring partial protection of mice immunized and challenged with lethal dose of N. caninum, while the JAC lectin showed no adequate adjuvant effect in the immunization against neosporosis.